Geopolítica de las emociones en prácticas educativas de territorios de posconflicto. Estudio comparativo entre México, Guatemala y Colombia (2020)
This article reflects on the role of emotions in the continuance of armed conflict and in peace-building from school. In this vein, the concepts of political emotions, geopolitics, and armed conflict are explored; then, reference is made to the context and pedagogical alternatives devised by communities in post-conflict territories in order to promote education for peace. This article seeks to present insights into the place of emotions in educational processes aimed at the culture of peace in areas affected by armed and social conflict; to this end, educational experiences located territorially in Chiapas (Mexico), Quiché (Guatemala), and Meta (Colombia) were analyzed and compared, so as to establish a geopolitics of emotions conducive to peace-building from education.